Before it is too late: current genetic diversity status of the exploited sandfish holothuria scabra (Echinodermata: Holothuroidea) - Khor, Waiho; Hanafiah Fazhan,; Fujaya, Yushinta; Chong, Alexander Shu-Chien; Muhammad Fatratullah Muhsin,; Suriyan Tunkijjanukij,; Nurul Hayati, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The sandfish Holothuria scabra is a well exploited and among the highest-valued sea cucumber species. Owing to its economic importance and the global expansion of sea cucumber fisheries that could lead to overfishing, the aquaculture of H. scabra is increasing rapidly. To aid in resource management and providing sufficient molecular information to inform the selection of sea cucumber broodstock to be incorporated into aquaculture, sufficient knowledge on their genetic diversity is among the pre-requisite. Therefore, this review synthesized together the currently available information on genetic diversity of H. scabra in a global scale, thereby highlighting the lack of genetic baseline of H. scabra in some populations. The implications and importance of the availability of genetic baseline data to restocking and sea ranching, fisheries, and aquaculture of H. scabra are discussed. Finally, future directions, including the development of full genome, the use of other sequencing technologies, and the impact of climate change onto H. scabra are provided.